DEVELOPMENT AND UTILIZATION OF THE PURWAREJA KLAMPOK-BANJARNEGARA RAILWAY LINE DURING THE DUTCH COLONIAL PERIOD, 1898-1942 - Iskandar; Aan Andriawan; Grizaldi Nauval Aalfaqih; Dwi Miftakhul Huda (RADJA PUBLIKA, 2026)
Banjarnegara is an area in the Banyumas Residency that is crossed by a railway line. The line was built during the Dutch colonial period. Traces of this line can still be seen today. This is why this research needs to be conducted, namely to find out (a) How was the railway line through Purwareja Klampok-Banjarnegara built? (b) How was the Purwareja Klampok-Banjarnegara railway line used? (c) What was the fate of the Purwareja Klampok-Banjarnegara line during the Dutch colonial period? This research was conducted using historical research methods. Historical research methods consist of several stages, namely topic selection, heuristics, verification, interpretation, and historiography. The results of this research are as follows: (a) The Purwareja Klampok-Banjarnegara line was part of a line operated by the Serajoedal Stoomtram Maatschappijj company, which was built in 1895 and completed in 1988. (b) The Purwareja Klampok-Banjarnegara line was used to transport industrial products, goods, and people, or for public transportation. (c) The Purwareja Klampok-Banjarnegara line ended with various problems, namely the Malaise and the Dutch East Indies occupation by Japan. Thus, the history of railways in Banjarnegara once had its heyday. In addition, the use of rail transportation was also quite important in supporting transportation modes in the region, boosting the community's economy, and contributing to national development efforts